Study of lead and cadmium accumulation in Marigold medicinal plant (Calendula officinalis) - Mehrab Yadegari; Samira Eskandari; Ramin Irani Pour (فیزیولوژی محیطی گیاهی, 2017)
Heavy metals are the most important bioenvironmental pollutants that are found in all industrial communities. The phytoremediation technique is applied to refine the land and reclaim contaminated soil from heavy metals. In order to evaluate the phytoremediation potential of Marigold plant against lead and cadmium heavy metals and their influence on growth, yield, and other characteristics of this plant, a pot experiment was carried out in a completely randomized design in a factorial layout with six replications at Research Field Municipal Parks and Green Spaces of Shahrekord during spring and summer of 2016. Treatments included different levels of cadmium (0, 5, 25, and 50 mg.kg-1 in dry soil) and lead (0, 40, 100, and 250 mg.kg-1 in dry soil). Results showed that different levels of lead and cadmium significantly affected morpho-physiological characteristics. Shoot and root dry and fresh weights and lead and cadmium accumulation in plant soil differed significantly. With an increase in heavy metal concentrations, shoot and root dry and fresh weights significantly decreased compared to the control plants. By adding cadmium concentration, the amount of cadmium in plant and available cadmium in soil increased and therefore translocated to aerial parts of plants along with the more lead. Results of this research showed that Marigold is a super accumulator plant that can accumulate cadmium and lead particularly in its aerial parts. The tolerance threshold in this plant was observed in the treatment containing combination of cadmium (up to 5 mg.kg-1) and lead (up to 250 mg.kg-1) of dry soil after which a decreasing trend was observed in most of the characteristics under study. It seems that negative effects of these heavy metals particularly cadmium is due to their effect on photosynthesis.